Penerapan Problem Based Learning (PBL) untuk Meningkatkan Higher Order Thinking Skills (HOTS) Ditinjau dari Hasil Belajar Mahasiswa pada Mata Kuliah Materi IPA MI - Muhamad Afandi; Tutut Handayani (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2020)
This study aims to: (1) Describe the application of probem based learning in improving the higher order thinking skills of students in MI science subject material; (2) Explain the increase in higher order student thinking skills in terms of learning outcomes after applying probem based learning in MI subject matter science subjects; (3) Analyzing the constraints faced in applying probem based learning in improving the higher order thinking skills of students in MI science subject matter. This study uses a Classroom Action Research (CAR) design. This research was carried out for three cycles. Each cycle consists of four stages of activity, namely: the planning stage, the implementation phase, the observation and evaluation stage, and the reflection phase. Data collection methods use observation, tests, interviews, and documentation. Data analysis includes reducing data, presenting data and drawing conclusions. The results of this study include: (1) Application of probem based learning in improving higher order thinking skills of students in MI subject matter subject matter is carried out with the following steps: opening learning, delivering learning material, orientation of problems to students, organizing students , guiding individual and group investigations, developing and presenting artifacts or exhibits, analyzing and evaluating problem solving processes, evaluating and reflecting learning, and closing learning; (2) The ability of higher order thinking skills of students in terms of learning outcomes in MI science subject matter increases in each cycle. In cycle I, the higher order thinking ability skills of students get a value of 65 with enough categories. In the second cycle increased to 70 with enough categories. Likewise, in the third cycle the value increased to 76 with a good category. Each increase in students' Higher Order Thinking Skills if calculated from cycle I to cycle II increased by 5, in cycle II to cycle III by 6, and if calculated overall from cycle I to cycle III increased by 11; (3) Constraints faced in applying probem based learning in improving students' higher order thinking skills in MI subject matter subjects are problems related to problem focus, formulating problems, managing group discussions, time management, and learning outcomes products.